2020
DOI: 10.1590/1806-93042020000300007
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal near miss and the occurrence of negative outcomes in the first year of life: data from a national survey, Nascer no Brasil (Born in Brazil), 2011-2012

Abstract: Objectives: estimate the strength of association between neonatal near miss and the nega-tive outcomes in the child’s first year of life. Methods: a prospective cohort study on neonatal survivors originating from a national survey “Nascer no Brasil (Born in Brazil), 2011-2012.” Main exposure: neonatal near miss (NNM). Negative outcomes: breastfeeding, hospitalization, and post neonatal death (tele-phone interview). For each outcome, the odds ratio (OR) were estimated by univariate (p<0.2) and multivariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…19 Although survivors of the neonatal period, NNM cases present higher mortality up to five incomplete years, especially in the post-neonatal period, 19 permanence of hospitalization for delivery, hospitalization after discharge from delivery, and weaning in the first year of life, evidencing conditions of vulnerability and the need for social assistance and support for their families. 30 Besides confirming the effect of low birth weight, prematurity, and asphyxia on neonatal death, this study identified that socioeconomic vulnerability markers -low education level and brown or black skin colors -were associated with neonatal death and NNM. Absent or inadequate prenatal care were strongly associated with both outcomes, being stronger for neonatal death.…”
Section: Fundingsupporting
confidence: 60%
“…19 Although survivors of the neonatal period, NNM cases present higher mortality up to five incomplete years, especially in the post-neonatal period, 19 permanence of hospitalization for delivery, hospitalization after discharge from delivery, and weaning in the first year of life, evidencing conditions of vulnerability and the need for social assistance and support for their families. 30 Besides confirming the effect of low birth weight, prematurity, and asphyxia on neonatal death, this study identified that socioeconomic vulnerability markers -low education level and brown or black skin colors -were associated with neonatal death and NNM. Absent or inadequate prenatal care were strongly associated with both outcomes, being stronger for neonatal death.…”
Section: Fundingsupporting
confidence: 60%
“…Neonatal intensive care units (NICUs) are intended for hospital care of patients between 0 and 28 days of life, 1 and neonatal hospitalization is mainly related to lower gestational age (GA), low birth weight, and need for oxygen therapy or ventilatory support, which are associated with higher neonatal morbidity and mortality. 2 - 4 …”
Section: Introductionmentioning
confidence: 99%
“…Neonatal intensive care units (NICUs) are intended for hospital care of patients between 0 and 28 days of life, 1 and neonatal hospitalization is mainly related to lower gestational age (GA), low birth weight, and need for oxygen therapy or ventilatory support, which are associated with higher neonatal morbidity and mortality. [2][3][4] Respiratory difficulty in this population occurs due to pulmonary and respiratory center immaturity, added to the anatomical disadvantages of the conduction airways, predisposing to asynchronous respiratory movements, respiratory pauses, and apneas. 5 Noninvasive ventilation (NIV) provides positive pressure to the airway via mask or nasal prong, acting to prevent and treat patients with respiratory distress (RD).…”
Section: Introductionmentioning
confidence: 99%